Selective versus Exclusive Use of Drug-Eluting Stents in Treating Multivessel Coronary Artery Disease: A Real-World Cohort Study - Karbassi, Arsha (Texas Heart® Institute, Houston, 2014)
There have been attempts to find new approaches to the treatment of multivessel coronary artery disease without increasing adverse events. Deployment of drug-eluting stents (DES) for complex lesions and bare-metal stents (BMS) for simpler lesions, although already in wide use, has not been well supported by clinical study. A cohort of 1,658 patients who underwent multivessel percutaneous coronary intervention from March 2003 through June 2011 was studied for 1 year. These patients were divided into 3 groups: BMS only (599 patients); DES only (481 patients); and hybrid stenting (578 patients). Baseline characteristics were similar except for hyperlipidemia and moderate-to-severe mitral regurgitation, which were more frequent in the DES and hybrid groups, respectively. Lesion characteristics were more complex in the DES group, compared with the other groups: more B2/C type lesions, longer stents, and smaller reference-vessel diameters (P <0.001). The rates of major adverse cardiac events (MACE) at 1 year were similar between the groups (BMS=5.2%, hybrid=3.9%, and DES=3.4%; P=0.248). Subgroup analysis yielded no differences in death, nonfatal myocardial infarction, target-vessel revascularization, or target-lesion revascularization. On multivariable analysis, the strongest predictors of 1-year MACE were percutaneous intervention complicated by dissection, renal failure, left ventricular ejection fraction below 0.40, mean lesion length, reference vessel diameter, and percutaneous intervention on the left circumflex coronary artery. The latter two had inverse relationships with MACE. In conclusion, implanting the DES for more complex lesions and the BMS for simpler lesions seems more sensible than the exclusive use of the DES or the BMS.